Genetic characterization of central Mediterranean stocks of the loggerhead turtle (Caretta caretta) using mitochondrial and nuclear markers, and conservation implications. Issue 6 (8th March 2013) - Garofalo, Luisa; Mastrogiacomo, Angela; Casale, Paolo; Carlini, Rossella; Eleni, Claudia; Freggi, Daniela; Gelli, Donatella; Knittweis, Leyla; Mifsud, Carmen; Mingozzi, Toni; Novarini, Nicola; Scaravelli, Dino; et al.
ABSTRACT In migratory species female‐ and male‐mediated gene flow are important for defining relevant Management Units, and for evaluating connectivity between these and their respective foraging grounds. The stock composition at five Mediterranean foraging areas was investigated by analysing variation in the mitochondrial D‐loop and six microsatellite loci in a sample of 268 loggerhead turtles (Caretta caretta) stranded or accidentally caught by fisheries. This involved a comprehensive Mixed Stock Analysis which considers also recent data from major rookeries in Libya and Turkey, and the generation of a standardized nomenclature of allele sizes at the microsatellite loci. The results indicate: that the north Adriatic, the Tunisian continental shelf, the waters around Malta and the Italian Ionian Sea represent important areas for the conservation of rookeries in Greece, Libya and Turkey, respectively; that waters off the Italian peninsula and the islands of Lampedusa and Malta are mainly inhabited by individuals of Mediterranean origin, with a major contribution from the nearest and largest colonies, while Atlantic turtles are restricted to the western areas; that specific migratory routes exist from rookeries to foraging grounds; a poor bi‐parental genetic structuring, which suggests a high male‐mediated gene flow in the Mediterranean; mixing of small turtles in waters distant from natal rookeries, and recovery of structuring for large‐sized individuals; and that uncommon mtDNA haplotypes are more powerful markers than microsatellite alleles in assessing an individual's origin, owing to their higher geographic specificity. Copyright © 2013 John Wiley & Sons, Ltd.